A theoretical DFT-based and experimental study of the transmetalation step in Au/Pd-mediated cross-coupling reactions - Hansmann, Max M.; Pernpointner, Markus; Döpp, René; Hashmi, A. Stephen K. (Chemistry - a European journal, 2013)
In this work a combined theoretical and experimental investigation of the cross-coupling reaction involving two metallic reaction centers, namely gold and palladium, is described. One metal center (Au) hereby is rather inert towards change in its oxidation state, whereas Pd undergoes oxidative insertion and reductive elimination steps. Detailed mechanistic and energetic studies of each individual step, with the focus on the key transmetalation step are presented and compared for different substrates and ligands on the catalytic Pd center. Different aryl halides (Cl, Br, I) and aryl triflates were investigated. Hereby the nature of the counteranion X turned out to be crucial. In the case of X=Cl and L=PMe3 the oxidative addition is rate-determining, whereas in the case of X=I the transmetalation step becomes rate-determining in the Au/Pd-cross-coupling mechanism. A variety of Au-Pd transmetalation reaction scenarios are discussed in detail, favoring a transition state with short intermetallic Au-Pd contacts. Furthermore, without a halide counteranion the transmetalation from gold(I) to palladium(II) is highly endothermic, which confirms our experimental findings that the coupling does not occur with aryl triflates and similar weakly coordinating counteranions—a conclusion that is essential in designing new Au-Pd catalytic cycles. In combination with experimental work, this corrects a previous report in the literature claiming a successful coupling potentially catalytic in both metals with weakly coordinating counteranions.